Shapes of сups from the Saltovo-Mayaki culture of the Middle Don - Suhanov, Evgenij Vladimirovic (History, Archeology and Ethnography of the Caucasus, 2021)
The article deals with the analysis of cup’s shapes of the Don Alans and their neighbors. The study was based on 186 vessels from cemeteries Dmitrievka, Nizhnie Lubyanki, Yutanovka, Chervonaya Gusarovka, and Mayatski complex. The methodology is based on the historical-and-cultural approach to the study of the vessel’s shape, developed by A. A. Bobrinsky and supplemented by his modern followers. The shapes of the cups were studied at three analysis levels. These are the study of general proportions, vessel’s structure, and parameters of vessel’s functional parts. The main result of this study is the identification of two traditions of сup shapes in the Middle Don. The first tradition is a relatively lower «body» and a relatively lower «shoulder/brachium». It is represented in cemeteries Nizhnie Lubyanki, Yutanovka, Chervonaya Gusarovka, and Mayatski complex. The second tradition is a relatively higher «body» and a relatively higher «shoulder/brachium». This tradition is only in Chervonaya Gusarovka. The article attempts a chronological analysis of identified traditions based on the materials of cemeteries Dmitrievkа and Chervonaya Gusarovka. The cups made with different violations of mass traditions are typical for both relatively earlier and relatively later stages of sites. Another picture was shown by the cups that strictly correspond to the mass tradition at all levels of analysis. Such vessels are most characteristic of the early stages of Dmitrievkа and Chervonaya Gusarovka cemeteries.